An unprecedented trinuclear FeII triazole-based complex exhibiting a concerted and complete sharp spin transition above room temperature. Issue 59 (11th July 2017) - Pittala, Narsimhulu; Thétiot, Franck; Charles, Catherine; Triki, Smail; Boukheddaden, Kamel; Chastanet, Guillaume; Marchivie, Mathieu
Abstract : We report a triazole-based trinuclear Fe II complex as the first example that displays a sharp and complete spin transition. The strong ferro-elastic coupling between the three metal centers was identified as the source of the concerted spin transition. Abstract : We report a triazole-based trinuclear complex as the first example that displays a complete one-step first-order [HS–HS–HS] ↔ [LS–LS–LS] spin transition at 318 K. The strong ferro-elastic interactions, between the three metal centers, have been identified as the source of the concerted spin transition in this trinuclear complex.